Anomalous tunneling of phonon excitations between two Bose-Einstein condensates. - Kagan, Y; Kovrizhin, D; Maksimov, L (2003)
We discuss the tunneling of phonon excitations across a potential barrier separating two condensates. It is shown that a strong barrier proves to be transparent for the excitations at low energy epsilon. Moreover, the transmission is reduced with increasing epsilon in contrast to the standard dependence. This anomalous behavior is due to the existence of a quasiresonance interaction. The origin of this interaction is a result of the formation of a special well determined by the density distribution of the condensate in the vicinity of a high barrier.